Vacation - Harold Ramis; Anthony, Michael Hall.; Beverly D'Angelo; Dana Barron; Eddie Bracken; Imogene Coca; Randy Quaid; Chevy Chase (USA Warner Bros. Pictures, 1983)
After winning a tour package in a game show, the bickering Griswald family carve a trail of destruction through England (where they knock over Stonehenge), France, Germany, and Italy. Somehow Ellen (Bevery D'Angelo), the mom, gets kidnapped by gangsters, leading to a car chase that reunites the family, despite their differences. It's hard to believe that National Lampoon's European Vacation is only the second of the Vacation movies; it has the exhausted pallor of the last of a long series of sequels, drained of all zest or original ideas. The charmless smirk of Chevy Chase, mechanical in its idiocy, hangs over European Vacation like a death mask. It's hard to believe that this hack was once the funny and sexy hero of Foul Play. D'Angelo keeps her chin up and gives the movie whatever class it may have; she deserves better.
The Griswold family's cross-country drive to the WallyWorld theme park proves to be much more arduous than they ever anticipated.
John Hughes
Languages : English, Spanish
Subtitles : Turkish, English, French, German,Dutch, Polish, Czech, Danish, Finnish, Greek, Hebrew, Icelandic, Norwegian, Swedish, Serbo-Croatian, Spanish, Italian, Portuguese
Keywords: Comedy; Adventure